IMPROVE Validation Study: Infant & Young Child Feeding Counseling - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
This dataset is generated from the research study conducted to assess the validity of survey questions about infant and young child feeding (IYCF) received based on maternal recall, using observations of home visits and community-based gatherings attended by mothers of children less than one year of age as the gold standard. The study sample included women with children 0-11 months of age who were visited at home by a frontline worker at least once during a 2-wk period. Frontline workers (FLWs), i.e., Anganwadi workers (AWW) and Accredited Social Health Activist (ASHA) were followed during home visits, and observations were made of the services provided, particularly whether IYCF counseling was provided, and the specific messages/information received. Mothers who were visited by the FLWs were then interviewed within 2 weeks following the observed visits to ask survey questions about receipt of IYCF counseling during the specific home visits. The validity of the survey questions was estimated by calculating the sensitivity, specificity, accuracy, and other measures. In addition, services provided during community events such as Village Health and Nutrition Day or other routine community-based events were observed to document different modalities available in communities through which women are likely to receive IYCF information. The study was conducted in the Samastipur district of Bihar, India, from August to September 2021. The study was led by the International Food Policy Research Institute (IFPRI), in collaboration with CARE India Solutions for Sustainable Development, Bihar, India.